A glimpse into employee proactive behavior: the followership perspective - Yalcinyigit, Serap; Karacay, Gaye (SPRINGER, 2025)
Organizational research pays significant attention to proactive behavior due to its potential to enhance both individual and organizational effectiveness. Especially in recent times, efforts have focused on explaining proactive behavior as a key characteristic of followership. This review thoroughly examines the current understanding, the role, and future directions of proactive behavior from the followership perspective. Drawing on a diverse array of peer-reviewed literature in the fields of management, psychology, and organizational behavior, this review synthesizes insights from 57 articles published between 2009 and 2024, identified using the rigorous Scientific Procedures and Rationales for Systematic Literature Reviews (SPAR-4-SLR) protocol. Initially, these articles underwent bibliometric analysis to provide a quantitative overview, followed by interpretive analysis to derive qualitative insights. The findings of these analyses highlight key themes such as followership identity, peer-level interactions, leader-member dyadic influence, and the organizational context. Moreover, as an outcome of this review process, proactive behavior from followership perspective has come out as an under researched area within extant literature and suggesting avenues for future research to enrich both theoretical understanding and practical implications in this domain.
Keywords: Followership; Proactive behavior; Systematic review; Leadership; Proactive; IMPLICIT LEADERSHIP; WORK; ANTECEDENTS; PERFORMANCE; CONDUCT; SCIENCE; SEEKING; MODEL; VOICE; SELF; Psychology